Town planning in Islamic Egypt Fustat as a model - Wafaa Adnan Hamid , Prof. Dr.; Alaa Hammad Raja, Asst.Prof. Dr. (lark, 2023)
In order to find out the most important achievements of the Islamic state, which contributed to its expansion, a real need arose to establish a number of cities, which became capitals of the Islamic state, as well as metropolises for the surrounding cities. In this research, we review the most important cities that were established in the Islamic state, and the process of choosing the appropriate planning for them Which is the basis for the success of these cities, and there are a number of factors that are taken into account when planning cities.There are a number of influences in choosing the sites of Islamic cities, the nature of which differed from one city to another, especially those factors related to the military or political aspects, and they agreed in the availability of basic conditions that must be met in general in choosing any site. These conditions are repeated in one form or another in the geographical sources that talk about the locations of cities and their good qualities.The mosque is the main axis that forms the center of the city to form the nucleus of urban change. Then, main roads were built to connect the mosque to the suburbs, and among the examples of the most prominent Islamic cities established by the Arab Muslims are many of them outside the Arabian Peninsula, the most important of which are Basra, Kufa, Fustat, Kairouan, Baghdad, Samarra and Cairo, and these cities were distinguished by landmarks that distinguished them from other cities.The nature of the research necessitated dividing it into an introduction to the nature of urban planning in the Arab Islamic state. Then, in the first topic, we discussed the main reasons and goals for the establishment of Islamic cities, cities outside the Arabian Peninsula. The second topic included the features of Islamic cities, which characterized the Islamic city with many landmarks that had a major role in the religious, social, economic, political, cultural and health life in the Islamic society. The third topic dealt with the cities in the Arab Islamic state (Al Fustat), while the fourth topic dealt with the planning of the city of Fustat. Then the research concluded with a set of findings.
Keywords: Building translation competence, sub-competencies of translation competence, communicative writing competence, Writing Course Design, Writing Assessment Form